2016
DOI: 10.1097/md.0000000000004587
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis complicating sarcoidosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In the present case, the therapy was initiated before obtaining the result of the cultural examination, which was probably a decisive factor concerning its prognosis. As evidenced in several cases, the early initiation of treatment has prognostic implications [1] . It should be noted that when the diagnosis of pulmonary cryptococcosis was made, dissemination to the CNS should had been excluded due to the need for more aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case, the therapy was initiated before obtaining the result of the cultural examination, which was probably a decisive factor concerning its prognosis. As evidenced in several cases, the early initiation of treatment has prognostic implications [1] . It should be noted that when the diagnosis of pulmonary cryptococcosis was made, dissemination to the CNS should had been excluded due to the need for more aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature conducted in 2016 by Leonhard et al, they found that the mean age of patients with sarcoidosis who developed cryptococcal meningitis was 39 years old and that 40% of patients were undergoing immunomodulatory therapy [1] . Our patient was well above this age group and has never been treated with systemic corticosteroid or other immunomodulators, which makes this case of particular interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptococcosis, an opportunistic infection caused by the encapsulated yeast Cryptococcus neoformans , is a rare but severe complication of sarcoidosis [1]. In a series of 40 sarcoidosis patients with cryptococcal meningitis — the most frequent manifestation of cryptococcosis — identified recently in the literature, 43% (17/40) had a delayed diagnosis, mainly because of initial suspicion of neurosarcoidosis [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 40 sarcoidosis patients with cryptococcal meningitis — the most frequent manifestation of cryptococcosis — identified recently in the literature, 43% (17/40) had a delayed diagnosis, mainly because of initial suspicion of neurosarcoidosis [1].…”
Section: Introductionmentioning
confidence: 99%